A Study on the Effects of Redundant Time on the Operation of Different Speed-Grade Trains in Passenger Railway Line Traffic System by Using Cellular Automata Model. (9th January 2014) - Zeng, Junwei; Qian, Yongsheng; Li, Wenjun; Guang, Xiaoping; Wang, Min
Abstract : As an integrated kind of railway signal-control pattern, the four-aspect fixed autoblock system has been used in many train control systems. This paper takes the four-aspect fixed autoblock system as the research object and proposes the cellular automata model of the fixed autoblock system based on the existing theoretical researches on different train systems and traffic systems by means of the analytical study of the classical cellular automata model. The CA (cellular automata) models combine complexity of passenger railway line with the theory of cellular automata and introduce some new CA models into the existing control systems. After analyzing the relevant simulation results, we study thoroughly and obtain efficiently the needed data for the variation of the section carrying capacity, the average train delay and the train speed which have been affected by redundant time on the operation of passenger trains with different speeds.